MEANING OF SPORT MONITORING AND ITS DEVELOPMENT TENDENCIES - Vītoliņš, Karlis; Fernāte, Andra; Kovaļovs, Atis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The earliest research on analytics in sports dates back to 1912 with the work by Hugh Fullerton on the correlation between baseball player hits, throws, and catching techniques, and success in the game. Nowadays with equally high technological and financial availability, the efficiency of the training process becomes more relevant. A well-organized and managed training process, combined with high technology and financial accessibility, will be the determining factor for successful performance. Research aim: to compare and analyse the meaning of sport monitoring and its development tendencies. Research methods: a systematic review of scientific literature was conducted, examining scientific articles available in the ScienceDirect and Google Scholar electronic databases (publishing date 2014-2024) using the following keywords: "monitoring", "sport monitoring”, “performance monitoring”, and “coaching monitoring". As a result of the study, the use of the term 'monitoring' in the context of the sport environment was clarified. The meaning and function of monitoring involves continuous systematic data collection based on selected criteria, with its most essential function being the ability to instantly inform involved parties about the characteristics of the performance process. Monitoring in sports is primarily applied in terms of athlete and team performance analytics. However, it is equally important to continuously and systematically observe the activities of coaches with the aim of providing feedback for improvement.